Meeting Point Of Values And Character Education In General Education - Ramadani, Andi Nur; Rettang, Lidia; Fajri, Nurul; Alam, Luktfy; Agus, Andi Aco; Najamuddin, Najamuddin (Jurnal Ilmiah Mandala Education (JIME), 2025)
Value and character education Value and character education is the main foundation in forming a moral and responsible generation. This study aims to explain the meeting point between value education and character education, especially in general education. The type of research used is descriptive qualitative research and uses a literature study research method carried out by processing data obtained from reviewing articles, journals and other sources related to the research. The results of the study show that the meeting point of value and character education in education can be found in various aspects such as: 1) application of values in students' daily lives; 2) Integration of value and character education in all subjects 3) education based on experience and exemplary behavior. In the development of value and character education, of course, there are various challenges in it so that effective strategies are needed to improve value and character education in general education such as training for educators, schools and parents need to work together and the curriculum must be well designed.